Mental health consequences of weight cycling in the first-year post-treatment for breast cancer. Issue 8 (3rd August 2018) - Pila, Eva; Sabiston, Catherine M.; Castonguay, Andrée L.; Arbour-Nicitopoulos, Kelly; Taylor, Valerie H.
Abstract : Objectives: Weight cycling is linked with advanced breast cancer diagnosis, increased risk of cancer reoccurrence and cancer-related mortality. While women treated for breast cancer report challenges with navigating their post-treatment body shape and weight, the effects of weight cycling on body image and mental health have not been elucidated. This study examined associations between weight changes and weight cycling on psychological health (i.e. weight-related guilt, shame and depressive symptoms) among women in the first-year post-treatment. Design and Outcome Measures: Self-reported assessments of pre-cancer weight cycling, post-treatment weight-related guilt, shame and depressive symptoms, and objective assessments of weight were assessed in a longitudinal sample of 173 women treated for breast cancer ( M age  = 55.01 ± 10.96 years). Results: Based on findings from multilevel models, women experienced the most weight-related shame when their weight was heavier than their personal average. Additionally, heavier weight was associated with worse psychological health, particularly for women with a history of stable (vs. cycling) weight pre-cancer. Conclusions: Weight cycling pre-cancer and post-treatment weight change have important implications for psychological well-being. Due to the potential psychological consequences associated with a history of weight cycling, targeted strategies are needed to improve overall health outcomes for women's survivorship after breast cancer.